1986
DOI: 10.1073/pnas.83.9.2865
|View full text |Cite
|
Sign up to set email alerts
|

Zero-order ultrasensitivity in the regulation of glycogen phosphorylase.

Abstract: The activity of glycogen phosphorylase (1,4-a-D-glucan:orthophosphate a-D-glucosyltransferase, EC 2.4.1.1) is controlled by a cyclic phosphorylation-dephosphorylation process through the action of the interconverting enzymes, phosphorylase b kinase (ATP:phosphorylase-b phosphotransferase, EC 2.7.1.38) and phosphorylase a phosphatase (phosphorylase a phosphohydrolase, EC 3.1.3.17). In muscle tissue, the combined concentration of the activated (phospho-) form, phosphorylase a, and the nonactivated (dephospho-) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 21 publications
4
39
0
Order By: Relevance
“…On that basis, we now reproduce the peculiar phenomenon of hypersensitivity in zero-order regime [7], confirming that our simplified kinetics reproduces effects of enzyme kinetics. In a hypersensitivity situation, a minor switch in relative enzyme quantities, creates a much amplified and sudden switch in two other quantities.…”
Section: Figure 14 Subtraction (Top)supporting
confidence: 66%
“…On that basis, we now reproduce the peculiar phenomenon of hypersensitivity in zero-order regime [7], confirming that our simplified kinetics reproduces effects of enzyme kinetics. In a hypersensitivity situation, a minor switch in relative enzyme quantities, creates a much amplified and sudden switch in two other quantities.…”
Section: Figure 14 Subtraction (Top)supporting
confidence: 66%
“…This result is a direct consequence of the saturation of the converter enzymes by their substrates, leading to a phenomenon known as &&zero-order ultrasensitivity'' (Goldbeter & Koshland, 1981), and of the cooperativity in the kinase activation by Ca> (Dupont & Goldbeter, 1992). Interestingly, in the case of muscle glycogen phosphorylase (Meinke et al, 1986), &&zero-order ultrasensitivity'' has indeed been demonstrated experimentally.…”
Section: E4ect Of Calcium Oscillations On Glycogen Phosphorylase Actimentioning
confidence: 81%
“…For one, none of the substrates can respond in a switch-like manner to incoming signals, so this mechanism cannot be deployed in cases where ultrasensitive responses are crucial (11,16,(44)(45)(46)(47). In addition, achieving fast dephosphorylation timescales may require high levels of phosphatase expression, which may become impractical (or limit the capacity of the system to respond at all) in cases where the K M needed to achieve insulation is very large (Figs.…”
Section: Removing Coupling With Unsaturatable Phosphatasesmentioning
confidence: 96%